Hematologic profiles of Plasmodium vivax Malaria patients - Gita Dwi Prasasty; Thia Prameswarie; Muhaimin Ramdja; Dwi Handayani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2018)
Abstract Background: Malaria infections cause various symptoms ranging from asymptomatic infections to severe disease complications. Plasmodium vivax malaria has been recognized as a disease that attacks blood cells, causing various hematologic changes, especially anemia, leukopenia, leukocytosis, neutropenia, neutrophilia, and thrombocytopenia with different percentages. Plasmodium vivax, formerly known to cause mild malaria, was later proven to cause severe malaria, even cerebral malaria such as Plasmodium falciparum. This study aims to determine the hematologic profile in patients with Plasmodium vivax malaria. Method: This research use descriptive cross sectional design. This research was conducted in Puskesmas (PKM; Primary Health Care) Sukamaju and Puskesmas (PKM; Primary Health Care) Karang City in August until December 2017. Samples were taken by consecutive sampling. A total of 37 samples expressed positive Plasmodium vivax, examined their hematologic profiles specifically hemoglobin, erythrocytes, leucocytes, platelets, lymphocytes, neutrophils, monocytes and hematocrit using automatic hematology cell counter. Results: Based on the results of this study, 56.76% of patients had anemia, 45.90% of patients had leukopenia, 89.20% thrombocytopenia, 2.70% neutrophilia, 10.80% neutropenia, 2.70% lymphocytosis, 35.10% lymphopenia, and 13.50% pancytopenia. Conclusion: In patients with Plasmodium vivax malaria infection there may be a change in hematologic profiles, this change may be affected by the acute phase of infection and host immune system. Keywords: Plasmodium vivax malaria, hematologic profiles